2012
DOI: 10.1016/j.jpainsymman.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Patient-Family Carer (Couple) Intervention for the Management of Symptoms and Other Health-Related Problems in People Affected by Cancer: A Systematic Literature Search and Narrative Review

Abstract: In the trials of cancer couple interventions included in the review, a pattern emerged of improvement in the emotional health of cancer patients and their carers when the intervention included support for the patient-family carer relationship. Further investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 34 publications
5
68
0
2
Order By: Relevance
“…For patient-partner dyads (couples), most research to date has explored experiences of breast or prostate cancer (Hopkinson et al, 2012). Colorectal (bowel) cancer is the third most common type of cancer within the UK, with increased incidence in recent years (Office for National Statistics, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For patient-partner dyads (couples), most research to date has explored experiences of breast or prostate cancer (Hopkinson et al, 2012). Colorectal (bowel) cancer is the third most common type of cancer within the UK, with increased incidence in recent years (Office for National Statistics, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review it was suggested that promoting healthy family dynamics through psychosocial treatment of both patient and caregiver helps caregivers cope, and may also be beneficial for the patient's (emotional) health (Hopkinson et al 2012). In providing support, it is important to realise that the needs of caregivers may differ from patients' needs at various time points (Collins et al 2014).…”
Section: Supportive Care and Interventions For Family Caregiversmentioning
confidence: 99%
“…Los descriptores utilizados para este fin fueron: "cancer and quality of life", "cancer and quality of life and review", "cancer and psychological intervention" y "cancer and psychological intervention and review". Además, con el objetivo de abarcar otros trabajos, incluso previos al año 2000, se han tenido en cuenta distintas revisiones publicadas por otros autores (5,7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . La revisión se realizó partiendo de los artículos originales, escritos en inglés y español y de los resúmenes ofrecidos en las bases de datos, en los que se especificase el procedimiento y la muestra del estudio.…”
Section: Métodounclassified